The future of inhalation therapy in chronic obstructive pulmonary disease - Mario Cazzola; Josuel Ora; Luigino Calzetta; Paola Rogliani; Maria Gabriella Matera (Elsevier, 2022)
The inhaled route is critical for the administration of drugs to treat patients suffering from COPD, but there is still an unmet need for new and innovative inhalers to address some limitations of existing products that do not make them suitable for many COPD patients. The treatment of COPD, currently limited to the use of bronchodilators, corticosteroids, and antibiotics, requires a significant expansion of the therapeutic armamentarium that is closely linked to the widening of knowledge on the pathogenesis and evolution of COPD. The great interest in the development of new drugs that may be able to interfere in the natural history of the disease is leading to the synthesis of numerous new molecules, of which however only a few have entered the stages of clinical development. On the other hand, further improvement of inhaled drug delivery could be an interesting possibility because it targets the organ of interest directly, requires significantly less drug to exert the pharmacological effect and, by lowering the amount of drug needed, reduces the cost of therapy. Unfortunately, however, the development of new inhaled drugs for use in COPD is currently too slow.